Analysis of normative documents on Environmental Education in Basic Education and the relationship with the teaching of chemistry and/or Nature Science Area (Research, Society and Development, 2022)
In the current context, there is an increasing need for reflections on Environmental Education (EE) in the school environment. Thus, this study aimed to analyze the legislation and regulation that regulate Brazilian education on Environmental Education in High School and the relationship with the Teaching of Chemistry and/or the Area of ​​Natural Sciences. The research is configured as a documentary study, with a qualitative approach, descriptive and exploratory in nature. The documents analyzed were: Law of Guidelines and Bases for National Education (LDB), the National Curriculum Guidelines (DCN), the Curriculum Guidelines for MS in Natural Sciences, Mathematics and its Technologies (OCEM), the National Curriculum Parameters for Education High School (PCNEM), the Common National Base (BNCC), the Curriculum Guidelines for Basic Education of Mato Grosso (OCEB-MT) and the Curriculum Reference Document for Mato Grosso High School stage (DRC/MT-EM). In summary, the set of documents that regulate EB in Brazil and Mato Grosso contribute to national and state public policies that govern and promote EE, which made it possible to carry out reflections regarding its effectiveness in teaching Chemistry and/or in the area of Natural Sciences, which can provide educational practices for understanding the relationship between society and the environment and possible changes in the attitudes of individuals.